PENAMBAHAN BRAIN GYM MENINGKATKAN FUNGSI KOGNITIF LANSIA: STUDI CROSS-SECTIONAL - Achmad Wisdin Wahyu Satria; Novita Sari Dewi; Lukman Faishal Fathrani (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: One of the issues that arise in the elderly is disturbance cognitive function  is marked by a decrease in cognitive function scores, specifically the MMSE (Mini-Mental State Examination) score. Brain Gym is one of the methods that can rejuvenate cognitive functions, however, some studies show that there are significant changes. Methods: The type of quasi-experimental research with a pretest and posttest approach with control group design. The population of this study was the elderly at the Pucang Gading Social Service Home, taken by purposive sampling as many as 32 elderly who were divided into two groups: control and intervention. Cognitive function was assessed using the Mini Mental State Examination (MMSE). The Mann Whitney test was used to analyze differences in changes in cognitive function between the elderly in the control and intervention groups. This research has received ethical approval. Results: Elderly gymnastics significantly increased the MMSE orientation subscale (p=0.001) but not significantly on the registration, attention and calculation, recall and language subscales (p>0.05). The addition of brain gym to elderly gymnastics can significantly increase the MMSE orientation and recall subscales (p<0.05), but not on the registration, attention and calculation, and language subscales (p>0.05). The increase in orientation, attention and calculation, and language functions was higher in the intervention group than in the control group. Conclusion: The addition of brain gym has an effect on increasing the cognitive function of the elderly at the Pucang Gading Social Service Home who receive elderly gymnastics.